2016
DOI: 10.3889/oamjms.2016.050
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Patterns, Breakfast Skipping and Familial Obesity among a Sample of Egyptian Families

Abstract: AIM:To examine the association between dietary patterns, behaviors and the prevalence of familial obesity.SUBJECTS AND METHODS:Eighty three families, shared as volunteers comprised of 83 mothers and 155 offspring. Anthropometric measurements were reported including height and weight. Body mass index (BMI), weight/height, and weight/height Z score were calculated. Pattern of food intake was obtained by means of dietary interview consisting of a 24 hour recall, and a food frequency questionnaire.RESULTS:Data rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In this study, 27% of the participants skipped breakfast, lower than that found between adolescents in other Brazilian studies (36.2% to 38%) [ 52 , 53 ]. Furthermore, we found a higher prevalence of breakfast skipping among participants with a family history for obesity (52.4%), similar to a study in Egypt [ 54 ], and despite that a higher prevalence of breakfast skipping among participants with acyanotic CHD (66.6%) was observed, no similar study was found for comparison.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, 27% of the participants skipped breakfast, lower than that found between adolescents in other Brazilian studies (36.2% to 38%) [ 52 , 53 ]. Furthermore, we found a higher prevalence of breakfast skipping among participants with a family history for obesity (52.4%), similar to a study in Egypt [ 54 ], and despite that a higher prevalence of breakfast skipping among participants with acyanotic CHD (66.6%) was observed, no similar study was found for comparison.…”
Section: Discussionsupporting
confidence: 68%
“…A similar practice of breakfast skipping among obese Egyptian mothers was previously reported, and was related to increased body weight. [45] Also breakfast composition was emphasized to contain more protein, fat and less carbohydrate which was consistent with Chandler-Laney et al, [46] who compared 2 types of diets; high carbohydrate/low fat breakfast, versus low carbohydrate/high fat breakfast. Low carbohydrate/high fat breakfast was associated with less hunger 3-4 hours after eating.…”
Section: Discussionsupporting
confidence: 65%
“…There are only limited studies investigating association between intake of naturally vitamin containing foods and vitamin deficiency in obesity (19)(20)(21). The objective of the present study was to compare the serum vitamin D, vitamin B12, and folic acid levels of nondiabetic obese patients and nonobese healthy controls, and to investigate the relationship between vitamin deficiencies, insulin resistance, and glucose metabolism.…”
Section: Introductionmentioning
confidence: 97%